Tanggung Jawab Notaris Terhadap Pemalsuan Akta Otentik Putusan Nomor : 933 K/Pid/2023 - Sofyan, Ferdi (Media Hukum Indonesia (MHI), 2025)
A notary is fundamentally a position that is legally binding, and the Notary Law (UUJN) regulates the oath of office that must be taken by a notary when performing their duties. The purpose of this thesis is to discuss the obligations of a notary, the research method used by the author, which is normative juridical, as well as to apply the theories of legal certainty and legal responsibility to address the issues in this research. The result of this research is that a notarial deed created can be annulled by the court based on Article 1266 of the Civil Code (KUHPer), as well as based on the court ruling Number 933 K/Pid/2023, which states that the judge sentenced the defendant to five years in prison. Therefore, in accordance with Article 13 of the UUJN, if a notary is sentenced to five years in prison, the notary may be dismissed dishonorably based on the proposal of the central notary supervisory council in the region where the defendant works as a notary.